Lesson of the month: novel method to quantify neutrophil uptake in early lung cancer using SPECT-CT. Issue 11 (4th September 2020) - Farahi, Neda; Gillett, Daniel; Southwood, Mark; Rassl, Doris; Tregay, Nicola; Hill, Uta; Preston, Stephen Denis; Loutsios, Chrystalla; Lok, Laurence Si Chong; Heard, Sarah; Buscombe, John; Rintoul, Robert Campbell; et al.
Abstract : Neutrophils play an important role in the lung tumour microenvironment. We hypothesised that radiolabelled neutrophils coupled to single-photon emission CT (SPECT) may non-invasively quantify neutrophil uptake in tumours from patients with non-small cell lung cancer. We demonstrated increased uptake of radiolabelled neutrophils from the blood into tumours compared with non-specific uptake using radiolabelled transferrin. Moreover, indium-111-neutrophil activity in the tumour biopsies also correlated with myeloperoxidase (MPO)-positive neutrophils. Our data support the utility of imaging with In-111-labelled neutrophils and SPECT-CT to quantify neutrophil uptake in lung cancer.